Management of Lepidocaryum tenue and Socratea exorrhiza, two Amazonian palms used for thatching - Navarro López, Jaime A.; Bernal, Rodrigo; Galeano, Gloria (Ethnobotany Research and Applications, 2020)
Background: The palms Lepidocaryum tenue and Socratea exorrhiza provide the raw material for one of the most prized thatches of the Colombian Amazon. Roofs thatched with Lepidocaryum leaves braided along split Socratea stems are highly appreciated and demanded by local inhabitants, due to their availability and freshness; as a result, both palms are an important source of cash income. Demand for Lepidocaryum roofs has increased, especially around the city of Leticia, due to population growth and tourism. Population size structure of both palms is similar to that reported in other places of the Amazon basin. Methods: Data were collected in five indigenous communities north of Leticia, Amazonas department (Colombia). In two communities we used participant observation to collect information about extraction practices and management processes. At all five places, we also conducted semi-structured surveys among 10 harvesters and 54 households, to learn about the harvest, management, and marketing of both species. Population size structure was evaluated at El Zafire Biological Station, where was selected 40 subplots of 0.01 ha for Lepidocaryum and 12 ha for Socratea. Results: Around 4000 harvestable individuals of Lepidocaryum and about six harvestable stems of Socratea were found per ha. Thatching a 48 m2 house requires ca. 1 ha of a forest with Socratea and 0.81 ha with Lepidocaryum. The traditional management practice is to harvest all but the three youngest leaves of Lepidocaryum, and selectively log the tallest individuals of Socratea (>15 m). We discuss the management practices of the involved species, as well as trade trends and resource supply in the area of Leticia. Conclusions: We recommend maintaining and extending traditional management practices. Nonetheless, due to overexploitation near human settlements, it is also necessary to recover the populations of both species, to guarantee the supply of raw material and prevent this economic activity from becoming unfeasible. Keywords: Arecaceae, harvest, non-timber forest products, shelter, trade.